2009
DOI: 10.1109/tdei.2009.5128508
|View full text |Cite
|
Sign up to set email alerts
|

Charging Characteristics of EPDM and Silicone Rubbers Deduced from Surface Potential Measurements

Abstract: Surface potential dynamics on corona charged surfaces of thick samples of EPDM and silicone rubbers have been studied and analyzed by examining the so called tdV/dt characteristics. This methodology allows for directly obtaining information about charge trap distributions in materials from measurements of potential decay without a-priori knowledge about trap parameters. More importantly, the combination of the above mentioned methodology in conjunction with measurements of other material parameters may provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(20 citation statements)
references
References 19 publications
(31 reference statements)
2
18
0
Order By: Relevance
“…Charge transportation was considered to be usually associated with carrier trapping and de-trapping [19]. The energy of the traps was related to time by considering so called demarcation energy E m , indicating the border between emptied and occupied traps [19].…”
Section: Mathematical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge transportation was considered to be usually associated with carrier trapping and de-trapping [19]. The energy of the traps was related to time by considering so called demarcation energy E m , indicating the border between emptied and occupied traps [19].…”
Section: Mathematical Treatmentmentioning
confidence: 99%
“…The energy of the traps was related to time by considering so called demarcation energy E m , indicating the border between emptied and occupied traps [19]. With increasing time, E m moves away from the conduction band and the relation between time and the energy gap is defined as…”
Section: Mathematical Treatmentmentioning
confidence: 99%
“…Thus most commercially available silicones are reinforced with a large amount of fumed silica (up to 40 wt%) to improve the mechanical and dielectric properties as well as to lower the cost 9 . Despite its technical importance, the charge transport properties in this type of silicone-based composite are rarely reported [9][10][11][12] . In this work, the high field charge transport of SiO 2 reinforced silicone rubber was comprehensively studied using pulsed electro-acoustic (PEA) space charge measurements and bulk dc current measurements in a range of fields until dielectric breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Gubanski et al reported spatial and temporal distributions of surface charge on ethylene propylene diene monomer rubber and SiR, with varying voltages and pulse numbers. They also investigated the mechanism of surface potential decay in high-temperature-vulcanized SiR in relation to air and bulk properties [9][10][11]. Li et al reported the charge transport of epoxy resin/glass composition (FR4), polytetrafluoroethylene and polyimide.…”
Section: Introductionmentioning
confidence: 99%